BIM integrated automation of whole building life cycle assessment using German LCA data base ÖKOBAUDAT and Industry Foundation Classes. Issue 3 (November 2020) - Theißen, S; Höper, J; Wimmer, R; Zibell, M; Meins-Becker, A; Rössig, S; Goitowski, S; Lambertz, M
Abstract: The life cycle assessment (LCA) of buildings is an important evaluation method for the environmental quality of buildings and their impact on climate and environment. However, this method is time-consuming and cost intensive. Building Information Modeling (BIM) has a high potential to integrate LCA into day-to-day planning. This research project aims to form the basis for BIM (semi) automation of whole building LCA by enabling the integration of LCA data using the Industry Foundation Classes (IFC). The DIN EN 15804 compliant and open access ÖKOBAUDAT is used as the database for LCA data. As a result, a BIM-LCA framework is proposed that includes the development of an Information Delivery Manual (IDM) describing the LCA according to a German assessment system for sustainable buildings (BNB). Based on this, a Model View Definition (MVD) is developed, which defines the software subset of an IFC data model to meet the exchange requirements (ER) for a whole building LCA. Solution approaches for adapting LCA databases and IFC 4 are presented. Finally, a first prototypical implementation of these results for the (semi) automation of whole building LCA is developed. In summary, the proposed IDM and MVD enable identifying the information exchange required to perform an LCA within a BIM-based environment. They also provide the background knowledge to develop a BIM tool to perform an LCA based on the framework proposed. Thereby, this research project contributes to achieve higher environmental quality of buildings by combining sustainable and digital planning methods.